On the Comparative Statics of a Competitive Industry with Inframarginal Firms - Panzar, John C.; Willig, Robert D. (American Economic Review, 2016)
Recently, economists have begun to develop a theory of the perfectly competitive firm and industry in long-run equilibrium.' In contrast to the traditional model2 in which all prices are parametric, this new theory takes explicit recognition of the fact that output price must adjust to exogenous changes in input prices before the industry can be said to be in long-run competitive equilibrium. The focus of this analysis has been to derive implications of competitive theory which can be tested using data generated by observing individual firms in